Nitrogen Source and External Medium pH Interaction Differentially Affects Root and Shoot Metabolism in Arabidopsis - Sarasketa, Asier; González-Moro, M. Begoña; González-Murua, Carmen; Marino, Daniel (Frontiers in Plant Science, 2016)
Ammonium nutrition often represents an important growth-limiting stress in plants. Some of the symptoms that plants present under ammonium nutrition have been associated with pH deregulation, in fact external medium pH control is known to improve plants ammonium tolerance. However, the way plant cell metabolism adjusts to these changes is not completely understood. Thus, in this work we focused on how Arabidopsis thaliana shoot and root respond to different nutritional regimes by varying the nitrogen source (NO3- and NH4+), concentration (2 and 10 mM) and pH of the external medium (5.7 and 6.7) to gain a deeper understanding of cell metabolic adaptation upon altering these environmental factors. The results obtained evidence changes in the response of ammonium assimilation machinery and of the anaplerotic enzymes associated to Tricarboxylic Acids (TCA) cycle in function of the plant organ, the nitrogen source and the degree of ammonium stress. A greater stress severity at pH 5.7 was related to NH4+ accumulation; this could not be circumvented in spite of the stimulation of glutamine synthetase, glutamate dehydrogenase and TCA cycle anaplerotic enzymes. Moreover, this study suggests specific functions for different gln and gdh isoforms based on the nutritional regime. Overall, NH4+ accumulation triggering ammonium stress appears to bear no relation to nitrogen assimilation impairment.